Mechanical properties of corroded carbon steel based on random pit corrosion in marine environment. (15th September 2022) - Jin, Libing; Zhang, Xiaowei; Liang, Xinya; Wang, Zhenqing; Wu, Qiang
Abstract: The corrosion of carbon steel seriously affects the long-term performance of the marine infrastructure. This study introduces an innovative numerical method for predicting the mechanical property degradation of carbon steel in the marine environment. To determine the degradation pattern of mechanical properties of carbon steel with various degrees of corrosion, 48 Q235 carbon steel specimens were subjected to mechanical properties testing after corrosion; a corrosion model with the stochastic distribution of corrosion pits was established based on the Monte-Carlo principle, and finite element analysis was carried out on the mechanical properties of carbon steel after corrosion. The numerical analytical results agreed well with the testing results, proving the model's validity and predicting the mechanical properties of carbon steel at various exposed times. The results demonstrate that as the amount of time exposed to specimens rises, the yield and tensile strength of the specimens decrease dramatically. Comparing the numerical simulation with the testing, the average error of the nominal tensile strength is 4.2%, and the average error of the nominal yield strength is 6.4%. It was further predicted that the specimens' nominal yield strength and nominal tensile strength decreased by 25.57% and 30.86% when the exposed time was 400 days. Highlights: In contrast to the previous works in the literature, the highlights of the manuscript can be summarized as follows: ● A corrosion model with the stochastic distribution of corrosion pits is established based on the Monte-Carlo principle. ● A combination of testing and numerical analysis is used to study the changes in the mechanical properties of carbon steel in the marine environment. ● A prediction for the degradation in mechanical properties of corroded carbon steel. ● The model can simulate the corrosion pattern of non-uniformly corroded carbon steel under chlorine salt environment more accurately, and has the prospect of application in engineering practice such as structural design and corrosion prevention.